Institutional Reforms and an Incredible Rise in Old Age Employment - Regina T. Riphahn; Rebecca Schrader (Center for Economic Studies and ifo Institute (CESifo), 2018)
We investigate whether a cut in unemployment benefit payout periods affected older workers' labor market transitions. We apply rich administrative data and exploit a difference-indifferences approach. We compare the reference group of 40-44 year olds with constant benefit payout periods to older treatment groups with reduced payout durations. For the latter job exit rates declined, job finding rates increased, the propensity to remain employed increased, and the propensity to remain unemployed declined after the reform. These patterns suggest that the reform of unemployment benefits may be one of the reasons behind the recent incredible rise in old age employment in Germany.
Keywords: J14; J26; 330; labor force participation; employment; unemployment insurance; retirement